Bioactivity and Therapeutic Potential of Kaempferol and Quercetin: New Insights for Plant and Human Health - Jan, Rahmatullah; Khan, Murtaza; Asaf, Sajjad; Lubna; Asif, Saleem; Kim, Kyung-Min (Plants (Basel), 2022)
Plant secondary metabolites, especially flavonoids, are major metabolites widely found in plants that play several key roles in plant defence and signalling in response to stress conditions. The most studied among these flavonoids are kaempferol and quercetin due to their anti-oxidative potential and their key roles in the defence system, making them more critical for plant adaptation in stress environments. Kaempferol and quercetin in plants have great therapeutic potential for human health. Despite being well-studied, some of their functional aspects regarding plants and human health need further evaluation. This review summarizes the emerging potential of kaempferol and quercetin in terms of antimicrobial activity, bioavailability and bioactivity in the human body as well as in the regulation of plant defence in response to stresses and as a signalling molecule in terms of hormonal modulation under stress conditions. We also evaluated the safe use of both metabolites in the pharmaceutical industry.